제주도 화산암의 총 공극률을 포함한 다양한 물리적 특성에 대한 일축압축강도의 특성 - 양순보; 문경태; 박상렬; 부상필; Yang, Soonbo; Moon, Kyoungtae; Park, Sangyeol; Boo, Sangpil (KSCE Journal of Civil and Environmental Engineering Research, 2024)
Jeju volcanic rock has a porous structure with irregularly developed vesicles of varying sizes and shapes, resulting from factors such as the physical properties of lava and its flow and cooling processes. Moreover, its mechanical properties exhibit regional variations. In this study, various laboratory tests were conducted on volcanic rock specimens from the northern part of Jeju Island. The relationships between various physical properties, including total porosity, and their correlations with uniaxial compressive strength were examined. The results confirmed that the relationship between absorption and bulk specific gravity of the Jeju volcanic rocks can be divided into two linear relationships (Linear Regression (1) and Linear Regression (2)). In contrast, there was a single linear relationship between total porosity and bulk specific gravity (or dry density) of the Jeju volcanic rocks. Regarding the relationships between uniaxial compressive strength and both bulk specific gravity and absorption of the Jeju volcanic rocks, each rock corresponding to either Linear Regression (1) or Linear Regression (2) exhibited different behaviors. However, unlike the above results, the relationship between uniaxial compressive strength and total porosity showed a single correlation, regardless of the two linear relationships between absorption and bulk specific gravity. 제주도 화산암은 용암의 물성, 용암의 유동·냉각 과정 등 여러 요인으로 인하여 다양한 크기 및 형상의 기공이 불규칙적으로 발달한 다공성 구조를 갖고 있으며, 역학적 특성 또한 지역마다 차이를 보이고 있다. 제주도 화산암의 물리·역학적 특성과 관련하여, 대부분의 연구는 화산암석의 다공성 구조를 나타내는 파라미터로서 열린 기공과 관련된 흡수율 또는 유효 공극률을 사용하고 있으며, 열린 기공과 닫힌 기공을 함께 반영하는 총 공극률과 관련된 연구는 거의 없는 실정이다. 본 연구에서는, 제주도 북부 지역에서 채취한 화산암을 대상으로 다양한 실내시험을 수행하였으며, 총 공극률을 포함한 다양한 물리적 특성 사이의 관계와 당해 물리적 특성과 일축압축강도와의 관계를 각각 살펴보았다. 그 결과, 제주도 화산암은 흡수율과 겉보기비중 사이의 관계에 있어서 크게 두 개의 선형 관계(선형 회귀 (1), 선형 회귀 (2))로 구분할 수 있음을 확인할 수 있었으며, 총 공극률과 겉보기비중(건조밀도)의 관계는 하나의 선형 관계로 나타낼 수 있음을 알 수 있었다. 제주도 화산암의 일축압축강도와 겉보기비중 및 흡수율의 각각의 관계에 있어서, 선형 회귀 (1) 또는 선형 회귀 (2)에 해당하는 각각의 암석은 서로 다른 거동을 보이고 있으며, 일축압축강도와 총 공극률의 관계는, 위의 결과와 달리 흡수율과 겉보기비중 사이의 두 개의 선형 관계와 상관없이 하나의 상관관계로 나타낼 수 있음을 알 수 있었다.